2020
DOI: 10.3390/ijms21176057
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis and Clinical Application of Growth-Factor-Independent In Vitro Myeloid Colony Formation in Chronic Myelomonocytic Leukemia

Abstract: We have originally reported that colony-forming units granulocyte/macrophage (CFU-GM) formation is an in vitro feature of chronic myelomonocytic leukemia (CMML) and a strong predictor for short survival. Elucidation of the molecular basis underlying this in vitro phenomenon could be helpful to define molecular features that predict inferior outcome in patients. We studied the correlation between the mutational landscape and spontaneous colony formation in 164 samples from 125 CMML patients. As compared to wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In this analysis NRAS mutations alone did not reach statistical significance as an independent factor impacting AML-free survival, however, the combined oncogenic RAS-pathway category including NRAS, KRAS and CBL was statistically significant in a model that only included genetic factors ( 74 ). Considering the fact, that spontaneous colony formation in CMML functionally covers the most frequent RASopathy gene mutations ( 38 ) these data are in line with findings in a small study which have been previously reported. In this study patients with CMML growth-factor-independent colony formation after transformation was significantly increased as compared to CFU-GM growth before transformation ( 37 ).…”
Section: Pathogenesis Of Cmmlsupporting
confidence: 91%
See 1 more Smart Citation
“…In this analysis NRAS mutations alone did not reach statistical significance as an independent factor impacting AML-free survival, however, the combined oncogenic RAS-pathway category including NRAS, KRAS and CBL was statistically significant in a model that only included genetic factors ( 74 ). Considering the fact, that spontaneous colony formation in CMML functionally covers the most frequent RASopathy gene mutations ( 38 ) these data are in line with findings in a small study which have been previously reported. In this study patients with CMML growth-factor-independent colony formation after transformation was significantly increased as compared to CFU-GM growth before transformation ( 37 ).…”
Section: Pathogenesis Of Cmmlsupporting
confidence: 91%
“…Moreover, the group in Vienna could show in a small retrospective study that CMML patients with high spontaneous CFU-GM growth (>100/10 5 PB mononuclear cells) have an inferior prognosis as compared to patients with low myeloid colony formation suggesting a clinical significance of the original observation (37). These results have been recently extended in a much larger CMML patient cohort indicating that spontaneous myeloid colony-formation was, compared to other single established prognostic factors, the strongest predictor regarding overall survival (OS) (38). This may indicate that in vitro cultures using unmanipulated mononuclear cells (MNC) may be a more global test that covers different aspects of malignancy better than any of the single parameters that are currently used to characterize the behavior of a tumor.…”
Section: Functional Analysis By In Vitro Studiesmentioning
confidence: 93%
“…We and others have shown that circulating blasts are an established adverse prognostic factor in patients with CMML [ 6 , 23 ]. We have recently demonstrated that a composite molecular parameter including NRAS/CBL/EZH2 , derived from its impact on spontaneous in vitro myeloid colony formation, was predictive for inferior survival as well as for an increased risk of transformation [ 26 ]. In the multivariable analysis reported by the Mayo group for their prognostic model, PB blasts but not BM blasts had a significant impact on leukemia-free survival [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic vitamin K-dependent proteins have been implicated as serine proteases in the coagulation system [88][89][90][91] .…”
Section: Discussionmentioning
confidence: 99%